Psychosocial Factors of Adolescent Cyberbullying: Social Anxiety, General Belongingness, and Social Connectedness - Wardani, Ria; Putri, Amanda (Borong Newinera Publisher, 2025)
Cyberbullying is a form of violence committed through electronic contact, either individually or in groups to harm others psychologically. This study examines the psychosocial factors behind the phenomenon of cyberbullying from the perspective of victims, perpetrators, and both victims and perpetrators, namely social anxiety, general belongingness, and social connectedness. Data were collected from 377 students aged 16-18 years by the use of purposive random sampling. All measuring instruments used were translated into Indonesian Language by a sworn translator, and the validity and reliability were tested. The results of data testing using hierarchical multiple regression show that psychosocial factors like general belongingness, social anxiety and social connectedness partially influence cyberbullying with the biggest role coming from general belongingness in a negative direction. Meanwhile, the results of simultaneous testing show that the role of social connectedness is not visible because it is dominated by general belongingness and social anxiety. The findings of the test using support vector machine (SVM-AI) clearly show that cyberbullying is a real phenomenon among teenagers. The psychosocial factors behind the phenomenon of cyberbullying are primarily driven by individual needs which not only require connectedness that meets the need for affiliation, but also relationships based on trust and care.